DNA Damage Repair and Current Therapeutic Approaches in Gastric Cancer: A Comprehensive Review - Wang, Menghui; Xie, Chuan (Frontiers in Genetics, 2022)
DNA in the cell is frequently damaged by endogenous and exogenous agents. However, comprehensive mechanisms to combat and repair DNA damage have evolved over time to ensure genomic stability and integrity. Improper DNA damage repair may result in a variety of diseases, including some types of tumours and autoimmune diseases. Therefore, DNA damage repair mechanisms have been proposed as novel antitumor drug targets. To date, a large number of drug targeting DNA damage mechanisms have been developed. For example, PARP inhibitors that elicit synthetic lethality are widely used in individualized cancer therapies. In this review, we describe the latent DNA damage repair mechanisms in gastric cancer, the types of DNA damage that can contribute to the development of gastric cancer, and new therapeutic approaches for gastric cancer that target DNA damage repair pathways.